The Correlation Between Critical Thinking Skills and The Learning Outcomes on Musculoskeletal System - Cindiati, Maya; Claudianingrum, Haslinda; Ramadhanty, Jihan Azhaar; Suprapto, Purwati Kuswarini; Diella, Dea (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2021)
Critical thinking skills is a most important aspect that must be owned by students in biology learning, especially in solving the problems that require alternative in-depth solutions and close to the problems that we are often encountered in daily life. This research aims to determine the correlation between student’s critical thinking skills and learning outcomes on the topic of human musculoskeletal system. The method for this research was correlational study. The research’s populations were all of grade 10 MIPA Senior High School in Tasikmalaya with characteristics discipline and have a lot of achievement in academic and nonacademic. The sample was 48 students from grade 10 of MIPA 4 selected based on cluster random sampling method. The data were gained by giving the essay test consisting of 15 analysis questions with indicators developed by Ennis to measure student’s critical thinking, and 35 multiple choice questions to measure student’s learning outcomes. Data analyzed by correlation and regression analysis Pearson product moment with significant level (α) 0,05. The normality and linearity test are conducted before performing the hypothesis test as a prerequisite. The result of research, data analysis, and hypothesis testing reveals that there is a positive correlation between student’s critical thinking skills and learning outcomes on the topic of human musculoskeletal system with correlation coefficient obtained is 0,667 it’s mean have a high correlation category. Contribution of critical thinking skills toward learning outcomes is 44,5% while 55,5% is influenced by other variables that are not researched.